HUBUNGAN GAYA KEPEMIMPINAN DENGAN MOTIVASI KERJA PERAWAT DI RSUD BATARA GURU BELOPA, LUWU - Yuliana Janur; Hidayat, Wahyu; Lindriani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Work motivation is a condition that has a strong influence in terms of generating or encouraging, guiding and maintaining related behavior in the work environment. While leadership style is a characteristic, habit, character and personality that is distinctive and unique from a leader so that it distinguishes it from others that colors the behavior and way that person leads. The low work motivation of nurses is usually caused by a very high workload, low salaries, and also because the leadership style tends to conflict with the character of their subordinates. The purpose of this study was to determine the relationship between leadership style and work motivation of nurses in the inpatient room at Batara Guru Belopa Hospital, Luwu Regency. The discussion compiled in this chapter includes the leadership style of the head of the room, work motivation of nurses and the relationship between leadership style and work motivation of nurses in the Inpatient Room of Batara Guru Belopa Hospital, Luwu Regency.